2013
DOI: 10.1161/circresaha.111.300448
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelin Axis Is Upregulated in Human and Rat Right Ventricular Hypertrophy

Abstract: −7,−6,−5 mol/L) decreased contractility in the hypertrophied, but not normal RV, in a dose-dependent manner (P<0.01). Conclusions:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 51 publications
4
56
1
Order By: Relevance
“…28 Recent work using rats with secondary PAH induced by ischemic heart failure has also shown that RV dysfunction is not improved by bosentan treatment. 29 The study by Nagendran et al 26 may partly explain why treatment with bosentan provides no significant improvement of RV dysfunction in PAH observed in those studies.…”
Section: Circulation Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…28 Recent work using rats with secondary PAH induced by ischemic heart failure has also shown that RV dysfunction is not improved by bosentan treatment. 29 The study by Nagendran et al 26 may partly explain why treatment with bosentan provides no significant improvement of RV dysfunction in PAH observed in those studies.…”
Section: Circulation Researchmentioning
confidence: 94%
“…25 Current treatment guidelines recommend these ERAs, especially for PAH patients in the World Health Organization (WHO) functional class III. 19 In the current issue of Circulation Research, Nagendran et al 26 demonstrate a compensatory role for the upregulated ET-1 axis to preserve RV contractility in RV hypertrophy. The authors found that bosentan and cyclo(Trp-Asp-Pro-ValLeu) (ET A receptor antagonist) decreased cardiac contractility in hypertrophied, but not normal rat RVs in a concentrationdependent manner.…”
mentioning
confidence: 95%
“…For example, sildenafil has been shown to increase RV inotropy, 37 and conversely agents like bosentan exert a negative effect on RV function. 38 We propose that when evaluating the effects of a pulmonary hypertension drug, researchers should look for a concomitant improvement in RV function. Alzoubi et al 39 reported that dehydroepiandrosterone (DHEA) reduced the severity and frequency of lung vascular occlusive lesions in the SuHx rat model of severe PAH, but, most importantly, treatment with DHEA also restored RV function, and this improvement was associated with recovery of the RV capillary density and reduced expression of apoptosis markers.…”
Section: The Lung Circulation-rv Axis: Implications For Future Therapiesmentioning
confidence: 99%
“…Endothelin Axis in RVH (p 347) 6 Drugs for lowering pulmonary artery blood pressure could have detrimental effects on the heart, say Nagendran et al…”
Section: Sarcolemmal Invaginations and Nuclear Camentioning
confidence: 99%